First chloroplast genome of Scleropyrum wallichianum (Cervantesiaceae) insights into phylogeny and conservation - THUY LIEN BUI; LINYUE HE; WYCKLIFFE OMONDI OMOLLO; SHENGDAN WU; BA CUONG CAO; XUAN THANH NGUYEN; XUAN THANH TRINH; PHI BANG CAO; NGAN THI LU; CHI TOAN LE (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Bui TL, He L, Omollo WO, Wu S, Cao BC, Nguyen XT, Trinh XT, Cao PB, Lu NT, Le CT. 2025. First chloroplast genome of Scleropyrum wallichianum (Cervantesiaceae) insights into phylogeny and conservation. Biodiversitas 26: 5763-5769. Scleropyrum wallichianum, a member of the family Cervantesiaceae (order Santalales), is distributed across Southeast Asia and China. The species is economically significant due to its seed oil, which is used in the production of lubricants and soap. In this study, the complete chloroplast genome of S. wallichianum was sequenced and analyzed to clarify its phylogenetic position within Santalales and to support conservation efforts. A leaf sample was collected from the Me Linh Station for Biodiversity in northern Vietnam. The genome was sequenced using the DNBSEQ-T7 platform, assembled with GetOrganelle, and annotated with CPGAVAS2, with manual correction of ambiguous regions performed in Apollo. The circular plastome was visualized using OrganellarGenomeDRAW. The assembled chloroplast genome, representing the first complete sequence reported for S. wallichianum, provides a valuable genomic resource for molecular systematics, evolutionary genomics, and conservation genetics of Cervantesiaceae and the order Santalales. The plastome exhibits a typical quadripartite structure with a total length of 149,066 bp and a GC content of 38.3%, comprising a Large Single-Copy (LSC) region of 85,000 bp, a Small Single-Copy (SSC) region of 18,500 bp, and two Inverted Repeats (IRs) of 22,783 bp each. Phylogenomic reconstruction based on 80 shared coding genes strongly supports S. wallichianum as a distinct clade within Cervantesiaceae, sister to Opiliaceae. This newly characterized plastome enriches the genomic resources available for the genus Scleropyrum and enhances understanding of the evolutionary history, taxonomy, and conservation genetics of Cervantesiaceae and related parasitic lineages within Santalales.